(untitled) (Annals of Medical Research, 2021)
Aim: Glutathione, which is known to be the main antioxidant, is the foremost redox regulator in the control of inflammatory processes. The goal of this study was to investigate the levels of total glutathione, which plays a central role in cellular antioxidant defense, in the gingival crevicular fluid (GCF) and plasma of individuals with gingivitis and periodontally healthy.